Designing a Long Acting Erythropoietin by Fusing Three Carboxyl-Terminal Peptides of Human Chorionic Gonadotropin β Subunit to the N-Terminal and C-Terminal Coding Sequence - Fuad Fares; Avri Havron; Eyal Fima (International Journal of Cell Biology)
A new analog of EPO was designed by fusing one and two CTPs to the N-terminal and C-terminal ends of EPO (EPO-(CTP)3), respectively. This analog was expressed and secreted efficiently in CHO cells. The in vitro test shows that the activity of EPO-(CTP)3 in TFI-1 cell proliferation assay is similar to that of EPO-WT and commercial rHEPO. However, in vivo studies indicated that treatment once a week with EPO-(CTP)3 (15 μg/kg) dramatically increased (~8 folds) haematocrit as it was compared to rHuEPO. Moreover, it was found that EPO-(CTP)3 is more effective than rHuEPO and Aranesp in increasing reticulocyte number in mice blood. The detected circulatory half-lives of rHuEPO, Aranesp, and EPO-(CTP)3 following IV injection of 20 IU were 4.4, 10.8, and 13.1 h, respectively. These data established the rational for using this chimera as a long-acting EPO analog in clinics. The therapeutic efficacy of EPO-CTP analog needs to be established in higher animals and in human clinical trials.